Does Ockham’s razor matter to the problem of universals? - de Alencar, Valdetonio Pereira (Griot : Revista de Filosofia, 2025)
This paper investigates how Ockham’s Razor can be applied to compare and evaluate solutions to the Problem of Universals. Initially, I discuss three formulations of this principle. Two kinds of parsimony emerge from this debate: ontological and ideological parsimony. Concerning the Problem of Universals, there are three groups of solutions: Realism, Nominalism, and Trope Theory. Analyzing the most parsimonious theory of each, in terms of ontological and ideological parsimony, yields a negative evaluation of the Razor. Ontological and ideological parsimony are not useful for determining whether one solution to the Problem of Universals is superior to another.